2020
DOI: 10.3390/metabo10090354
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Angiopoietin-Like Protein 4 and Glucose Metabolism in Older Adults after Exercise and Weight Loss

Abstract: Angiopoietin-like protein 4 (ANGPTL4) is an adipokine that plays an important role in energy homoeostasis and lipid and lipoprotein metabolism. This study was designed to determine the effect of an exercise plus weight loss intervention on ANGPTL4 expression and its relationship with metabolic health. Thirty-five obese sedentary men (n = 18) and postmenopausal women (n = 17), (X ± SEM, age: 61 ± 1 years, BMI: 31.3 ± 0.7 kg/m2, VO2max: 21.7 ± 0.9 L/kg/min) completed a 6 month program of 3×/week aerobic exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…However, there is a lack of knowledge of basal and hyperinsulinemic SIRT1 and SIRT3 expression and association with insulin sensitivity in older adults. Finally, we have previously shown higher fitness levels in men and smaller body fat percentage than women of comparable BMI and fat mass, 10 as well as greater insulin resistance in older men than women even after controlling for abdominal fat 11 suggesting that other metabolic factors influence differentiations in insulin sensitivity by sex. Furthermore, others report gender differences in serum SIRT1 12 which may explain gender differences in atherosclerotic cardiovascular disease 13 suggesting the hypothesis that there are sex differences in sirtuins in skeletal muscle.…”
Section: Impact Statementmentioning
confidence: 81%
“…However, there is a lack of knowledge of basal and hyperinsulinemic SIRT1 and SIRT3 expression and association with insulin sensitivity in older adults. Finally, we have previously shown higher fitness levels in men and smaller body fat percentage than women of comparable BMI and fat mass, 10 as well as greater insulin resistance in older men than women even after controlling for abdominal fat 11 suggesting that other metabolic factors influence differentiations in insulin sensitivity by sex. Furthermore, others report gender differences in serum SIRT1 12 which may explain gender differences in atherosclerotic cardiovascular disease 13 suggesting the hypothesis that there are sex differences in sirtuins in skeletal muscle.…”
Section: Impact Statementmentioning
confidence: 81%
“…Metabolic stresses, such as acute bouts of exercise, fasting and caloric restriction, induce the expression of ANGPTL4 in human skeletal muscle (Catoire et al, 2014), likely by increasing plasma free-fatty acid levels and activating the peroxisome proliferator-activated receptor-δ (PPAR-δ) (Staiger et al, 2009). ANGPTL4 stimulates lipolysis in WAT, determining a shift from fat storage to fat release, and triggers AMP-activated protein kinase (AMPK) in skeletal muscle, thereby mediating an increase in its mitochondrial oxidative capacity and ATP production (Norheim et al, 2014;Chang et al, 2018;Li et al, 2020). It should be noted that besides skeletal muscle, adipose tissue and the liver express higher levels of ANGPTL4 following exercise, likely contributing even more than skeletal muscle to ANGPTL4 exercise-mediated effects (Norheim et al, 2014).…”
Section: Myokines As Mediators Of Metabolic Reprogrammingmentioning
confidence: 99%
“…It should be noted that besides skeletal muscle, adipose tissue and the liver express higher levels of ANGPTL4 following exercise, likely contributing even more than skeletal muscle to ANGPTL4 exercise-mediated effects (Norheim et al, 2014). Interestingly, human studies showed that ANGPTL4 mRNA in skeletal muscle is lower in men than in women at basal conditions, probably due to differences in the utilization of glucose and fat mass in the two genders (Barja-Fernandez et al, 2018;Li et al, 2020). Moreover, a positive correlation between muscle ANGPTL4, obesity and glucose metabolism has been reported: indeed, ANGPTL4 muscle and serum levels are significantly higher in obese patients with an abnormal glucose tolerance (Barja-Fernandez et al, 2018;Li et al, 2020).…”
Section: Myokines As Mediators Of Metabolic Reprogrammingmentioning
confidence: 99%
“…Although its relevance in metabolic disorders of this hepatokine is not clear, it is well established that the protein regulates lipid metabolism by stimulating lipolysis in adipocytes [ 154 ] and inhibiting lipoprotein lipase activity [ 155 ]. Studies performed in humans have demonstrated that systemic ANGPLT4 increases during fasting and is secreted from the liver after exercise [ 156 ].…”
Section: Exercise Activates Liver-muscle Signaling Pathways Involvmentioning
confidence: 99%
“…The relationship of ANGPL4 with insulin resistance improvement after exercise is not clear. It has been reported that, in obese people, a 6-month program of exercise and diet did not change ANGPTL4 serum levels indicating that other factors contribute to the insulin sensitivity improvement found after this program [ 156 ]. However, other studies have shown increased levels of ANGPTL4 after fasting, chronic CR and endurance exercise in a response associated with the increase of plasma free fatty acids levels [ 153 ].…”
Section: Exercise Activates Liver-muscle Signaling Pathways Involvmentioning
confidence: 99%